Assessment of Bacterial Isolates from the Urine Specimens of Urinary Tract Infected Patient. (27th July 2022) - Prasada Rao, Chennu M. M.; Vennila, T.; Kosanam, Sreya; Ponsudha, P.; Suriyakrishnaan, K.; Alarfaj, Abdullah A.; Hirad, Abdurahman Hajinur; Sundaram, S. R.; Surendhar, P. A.; Selvam, Nagarajan
Abstract : Urinary tract infections (UTIs) maintained a serious public health concern, as did the growth in antibiotic resistance both between uropathogenic microorganisms. A regular assessment of the microbiological agents that cause UTIs, as well as their antimicrobial resistance, is essential for a tailored empirical antibiotic response. Knowing the variables that cause UTIs can help you intervene quickly and simply to get the condition under control. The most common infecting species in acute infection is Escherichia coli (E. coli). To strengthen infection control strategies, it is necessary to know the prevalence and location of UTI. The goal of this research is to measure the frequency of microorganisms isolated from patients with UTIs as well as the antimicrobial sensitivity characteristics of Gram-negative bacteria. The purpose of this research has been to evaluate the frequency of UTIs by extracting and characterizing the various bacterial etiological organisms, as well as to assess the factors linked to UTIs. The goal of this research is to identify, characterize, and establish the antibiotic susceptibility patterns of bacteria linked to urinary tract infections. Fresh collected urine specimen was taken from inpatients or outpatients in UTI cases and bacteriologically tested using conventional microbiological methods. The Kirby-Bauer disc diffusion method was used to create the antibiogram. Staphylococcus saprophyticus, Staphylococcus aureus (28%), and Escherichia coli (24.6%) were the most common isolates (20%). The evaluated agents' antibacterial activity was all in the following order: cefixime, ciprofloxacin, augmentin, gentamicin, ceftazidime, nitrofurantoin, ofloxacin, and cefuroxime. It was discovered that each and every one of the microbes exhibited varied degrees of resistance to the antibiotics nitrofurantoin, ciprofloxacin, and ofloxacin. Every type of bacteria, with the exception of those belonging to the genus Streptococcus, has a Multiple Antibiotic Resistance Index (MARI) that is more than 0.2. The first-line therapies for urinary tract infections (UTIs) in the region would consist of ciprofloxacin, ofloxacin, and nitrofurantoin. Lower urinary tract infections almost never result in problems if they are diagnosed and treated as soon as possible and in the correct manner. However, if treatment is not sought, a urinary tract infection can lead to serious complications.